Increasing Understanding of Food Security Program in Malaka District on the Nusa Tenggara Timur Border Between Indonesia and Timor Leste - Posma Sariguna Johnson Kennedy (Yayasan Literasi Sains Indonesia, 2022)
Food security is closely related to health, one aspect of well-being and the main focus of human development. Efforts to avoid food insecurity are experienced in areas with natural conditions and relatively little rainfall, such as the Nusa Tenggara Timur Province, especially in the Malaka Regency, the border area of Indonesia-Timor Leste. This community service activity aims to deepen understanding of Malaka Regency has food security by looking at the Malaka Agricultural Revolution Program (RPM), the policy to increase community economic productivity. We are writing this activity with a descriptive method using a simple qualitative approach. Data sources come from various literature and discussions with the government (Bupati) and the people of Malaka Regency. The RPM program positively impacts agronomic performance (rice, corn, and shallots) so that it can increase productivity, agricultural production, income and community welfare. However, there are still factors that hinder the implementation of the RPM Program, including internal factors (knowledge, skills and attitudes of farmers in dealing with changes brought about by the RPM program) and external factors (climate, availability of fertilizers, technology, etc).